Development of a PET/OMRI combined system for simultaneous imaging of positron and free radical probes for small animals. Issue 10 (27th September 2016) - Yamamoto, Seiichi; Watabe, Tadashi; Ikeda, Hayato; Kanai, Yasukazu; Ichikawa, Kazuhiro; Nakao, Motonao; Kato, Katsuhiko; Hatazawa, Jun
Abstract : Purpose: Positron emission tomography (PET) has high sensitivity for imaging radioactive tracer distributions in subjects. However, it is not possible to image free radical distribution in a subject by PET. Since free radicals are quite reactive, they are related to many diseases, including but not limited to cancer, inflammation, strokes, and heart disease. The Overhauser enhanced magnetic resonance imaging (OMRI) is so far the only method that images free radical distribution in vivo . By combining PET and OMRI, a new hybrid imaging modality might be developed that can simultaneously image the radioactive tracer and free radical distributions. For this purpose, the authors developed a PET/OMRI combined system for small animals. Methods: The developed PET/OMRI system used an optical fiber‐based PET system combined with a permanent magnet‐based OMRI system. The optical fiber‐based PET system uses flexible optical fiber bundles. Eight optical fiber‐based block detectors were arranged in a 56 mm diameter ring to form a PET system. The LGSO blocks were located inside the field‐of‐view (FOV) of the OMRI, and the position sensitive photomultiplier tubes were positioned behind the OMRI to minimize the interference between the PET and the OMRI. The OMRI system used a 0.0165 T permanent magnet. The system has an electron spin resonance coil to enhance the MRI signal using the Overhauser effect to image the free radical in the FOV of the PET/OMRI system. Results: The spatial resolution and sensitivity of the optical fiber‐based PET system were 1.2 mm FWHM and 1.2% at the central FOV, respectively. The OMRI system imaged the distribution of a nitroxyl radical (NXR) solution. The interference between PET and OMRI was small. Simultaneous imaging of the positron radiotracer and the NXR solution was successfully conducted with the developed PET/OMRI system for phantom and small animal studies. Conclusions: The authors developed a PET/OMRI combined system with the potential to provide interesting new results in molecular imaging research, such as in vivo molecular and free radical distributions.